Pengembangan Modul Ajar Akomodatif Berbasis Deep Learning Untuk Anak Berkebutuhan Khusus Di Sekolah Inklusi - Hidayati, Nurul; Amelia Rizky Idhartono; Novriyana Santri Yasin; Diana Wafiqah Kamilah (Universitas PGRI Adi Buana Surabaya, 2026)
The development of digital technology opens up new opportunities for developing more adaptive and personalized teaching modules. One rapidly developing technology is artificial intelligence (AI), particularly deep learning. In the educational context, this technology can be utilized to more accurately understand students' learning characteristics. Technological advancements have made learning easier for everyone, including people with disabilities. The Surabaya City Education Office is the partner for this Community Service (PkM) activity, involving 59 inclusive junior high school teachers. This activity was held on October 14-15, 2025. The lecturers also involved two students from the Special Education Study Program at PGRI Adi Buana University, Surabaya.